Spore-Based Probiotic Bacillus subtilis: Current Applications in Humans and Future Perspectives - Natasha Williams; Tiffany L. Weir (Fermentation, 2024)
Bacillus subtilis has been used for more than 50 years in many different industrial applications, including farming, precision fermentation, and probiotic supplements. It is particularly attractive as a probiotic because of its ability to form shelf-stable, acid-resistant spores that lend to diverse applications in the food system. B. subtilis is the most ubiquitous species of the genus and can be isolated from a broad variety of environments including animal and human gastrointestinal (GI) tracts. This is a comprehensive review of human intervention studies utilizing B. subtilis as a probiotic for supporting gastrointestinal health, as well as the reported impacts of B. subtilis use on the human gut microbiota and other biomarkers of health. It briefly covers the fate of ingested spores in the GI tract, summarizes the observed effects of different probiotic B. subtilis strains, and offers a perspective for the continued and future uses of B. subtilis in human applications.